A high-fat diet is associated with otitis media with effusion. Issue 12 (December 2015) - Choi, Hyo Geun; Sim, Songyong; Kim, So Young; Lee, Hyo-Jeong
Abstract: Objective: An association between obesity and otitis media with effusion (OME) has been previously reported. The aim of this study was to evaluate the association between dietary intake and OME when adjusting obesity. Methods: We analyzed the differences in dietary intake between children with/without OME who were 4 through 13 years of age using data from a large population-based survey – the Korea National Health and Nutrition Examination Survey – from 2008 through 2012. Data from 4359 participants were analyzed using simple and multiple logistic regression analyses with complex sampling. Results: The BMI category, the proportion of total calorie intake, protein intake, water intake, and Na intake (intake/recommendation), and the distribution of carbohydrate intake were not associated with OME. The distribution of fat intake was associated with OME (each 10% increase of fat calories/total calories: unadjusted odds ratio [OR] = 1.331, 95% confidence interval [CI] = 1.016–1.744, P  = 0.038; age- and sex-adjusted OR = 1.359, 95% CI = 1.028–1.797, P  = 0.031; adjusted for age, sex and other factors OR = 1.392, 95% CI = 1.054–1.839, P  = 0.020). Based on BMI subgroup analysis, the distribution of fat intake was associated with OME in the healthy weight group (each 10% increase of fat calories/total calories: unadjusted OR = 1.393, 95% CI = 1.017–1.909, P  = 0.039; adjusted OR = 1.470, 95% CI = 1.051–2.055, P  = 0.024) but not in the obese group. Conclusions: A high-fat diet was associated with OME and may represent a confounding factor between obesity and OME.